Modeling The Fate of Sumatran Elephants in Bukit Tigapuluh Indonesia: Research Needs & Implications for Population Management - Alexander Markus Moßbrucker; Muhammad Ali Imron; Satyawan Pudyatmoko; Peter-Hinrich Pratje; Sumardi Sumardi (Jurnal Ilmu Kehutanan)
The critically endangered Sumatran elephant persists in mainly small and isolated populations that may require intensive management to be viable in the long term. Population Viability Analysis (PVA) provides the opportunity to evaluate conservation strategies and objectives prior to implementation, which can be very valuable for site managers by supporting their decision making process. This study applies PVA to a local population of Sumatran elephants roaming the Bukit Tigapuluh landscape, Sumatra, with the main goal to explore the impact of pre-selected conservation measures and population scenarios on both population growth rate and extinction probability. Sensitivity testing revealed considerable parameter uncertainties that should be addressed by targeted research projects in order to improve the predictive power of the baseline population model. Given that further habitat destruction can be prevented, containing illegal killings appears to be of highest priority among the tested conservation measures and represents a mandatory pre-condition for activities addressing inbreeding depression such as elephant translocation or the establishment of a conservation corridor.